2006
DOI: 10.1016/j.mineng.2005.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study of the optimal distribution of cyanide in a gold leaching circuit

Abstract: The mineral industry has been using cyanidation to recover gold from ores for more than a century; however, a systematic study of the best reactant addition strategy in a cascade of agitated leaching tanks is not available in the open literature. A phenomenological mathematical model of the gold cyanidation process, calibrated with a set of industrial data from an Australian plant, together with an economic performance index is used to analyze this problem. The simulated results show that the best compromise b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 15 publications
0
52
0
Order By: Relevance
“…The first one explains the constant rate of cyanide consumption by copper and iron minerals and the second explains the effect of cyanide consumption proportional to the free cyanide content, such as the losses by hydrolysis to hydrogen cyanide and ammonia and the oxidation to cyanate or cyanogen; the rate of consumption is thus (Adams, 1990;de Andrade Lima, 2001;de Andrade Lima et al, 2002;de Andrade Lima and Hodouin, 2006):…”
Section: C) Free Cyanide Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first one explains the constant rate of cyanide consumption by copper and iron minerals and the second explains the effect of cyanide consumption proportional to the free cyanide content, such as the losses by hydrolysis to hydrogen cyanide and ammonia and the oxidation to cyanate or cyanogen; the rate of consumption is thus (Adams, 1990;de Andrade Lima, 2001;de Andrade Lima et al, 2002;de Andrade Lima and Hodouin, 2006):…”
Section: C) Free Cyanide Consumptionmentioning
confidence: 99%
“…The equations that describe the CIL and only leaching process are calibrated with the data from a plant that treats about 400 t/h of ore coming from twelve deposits located in the Eastern Goldfields Province, Yilgarn Craton, Western Australia (Roberts and Elias, 1990;Bax, 1996;de Andrade Lima, 2001;de Andrade Lima and Hodouin, 2006). The ore contains basalt and small amounts of marcassite (FeS 2 ), pyrite (FeS 2 ), chalcopyrite (CuFeS 2 ), galena (PbS), sphalerite (ZnS), gersdorffite (NiAsS), arsenopyrite (FeAsS), and pyrrhotite (Fe 1-x S), but the reactive sulfides content is very low (Roberts and Elias, 1990;Bax, 1996).…”
Section: Model Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wadsworth et al (2000) proposed a mechanistic model in which the surface reactions were thought to control the gold dissolution rate kinetically. Afterward De Andrade Lima and Hodouin (2006) proposed a mechanistic model of GCLP that consisted of mass conservation equations of gold in the solid phase, gold in the liquid phase and cyanide in the liquid phase. Therein the kinetic models of gold dissolution and cyanide consumption were identified with a set of industrial data from an Australian plant.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the best configuration was not identical for different gold content and cyanide concentration. A systematic study of the optimal distribution of cyanide in a cascade of leaching tanks was performed by De Andrade Lima and Hodouin (2006). However, the above optimization problems are only the simulation studies based on a fixed mechanistic model, which are difficult to be applied in industrial practice.…”
Section: Introductionmentioning
confidence: 99%